2022
DOI: 10.1002/ptr.7620
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of curcumin on ischemia/reperfusion injury

Abstract: Ischemia/reperfusion (I/R) injury is a term used to describe phenomena connected to the dysfunction of various tissue damage due to reperfusion after ischemic injury.While I/R may result in systemic inflammatory response syndrome or multiple organ dysfunction syndrome, there is still a long way to improve therapeutic outcomes. A number of cellular metabolic and ultrastructural alterations occur by prolonged ischemia. Ischemia increases the expression of proinflammatory gene products and bioactive substances wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 268 publications
(351 reference statements)
0
7
0
Order By: Relevance
“…Histopathological evaluation indicated that hesperitin alleviated IR-induced kidney injury in mice. Treatment of mice with hesperetin significantly reduced renal injury (P<0.05) in comparison to the IR group [27]. Histopathological examination of the mouse kidney tissue showed swelling and cystic renal tubule; dilatation with interstitial inflammation were apparent when contrast with the sham group.…”
Section: Effect Of Hesperetin On Renal Parenchymamentioning
confidence: 84%
“…Histopathological evaluation indicated that hesperitin alleviated IR-induced kidney injury in mice. Treatment of mice with hesperetin significantly reduced renal injury (P<0.05) in comparison to the IR group [27]. Histopathological examination of the mouse kidney tissue showed swelling and cystic renal tubule; dilatation with interstitial inflammation were apparent when contrast with the sham group.…”
Section: Effect Of Hesperetin On Renal Parenchymamentioning
confidence: 84%
“…Especially in hepatic ischemia models, many studies have been carried out and many agents have been used to minimize the resulting ischemic liver injury and subsequent reperfusion injury. However, since liver ischemia-reperfusion injury has not been clari ed yet, it is important to understand the pathophysiology of liver I/R-related diseases in the clinic and to reveal different treatment modalities for these diseases (Mohamadian et al 2022).…”
Section: )mentioning
confidence: 99%
“…Physiotherapy needs professional medical equipments and it usually acts affiliated role in treating IRI. Although pharmacological therapies are various, combinating different mechanisms drugs can exert the best therapeutic effectiveness and some of these durgs have serious side effects ( Mohamadian et al, 2022 ). However, as a classic and popular type of TCM, curcumin has gained a great attention for its multiple mechanisms such as antioxidant, anti-inflammatory, suppressing Ca 2+ overload and mediating autophagy et al Therefore, due to its distinctive and various pharmacological properties, curcumin might be the promosing candidate for the treatment of IRI.…”
Section: Therapeutic Approaches For Irimentioning
confidence: 99%
“…2 Therapeutic approaches for IRI Current therapeutic approaches are various and its foundations are alleviating ischemia and restoring reperfusion (Mohamadian et al, 2022). Therapeutic approaches can be divided into surgery, physiotherapy and pharmacology.…”
Section: Introductionmentioning
confidence: 99%